Imaginarios acerca de la violencia de género en jóvenes entre 14 y 20 años del sector Chilibulo - Corral Corral, Daniela Carolina (2015)
Understand the subjectivity implies that a psychological study must encompass the fields of interaction between the personalities and the world. The social imaginary has a series of performances and set of schemas that are instituting forms of life, relationship and action of the subject. The understanding of the world which is full of unknown aspects is generated in this articulation through representation. The representations and meanings mobilized emotions and attitudes, but is based on conceptions on some phenomenon that translates into knowledge. From this perspective the knowledge flows in the ways of conceiving the world and become structural aspects within social relations. The construction of gender and the determination of distinctive roles for men and women gives an account of the social and political construction, since it is based on relations of hierarchy and power that throughout history has been playing in practices of discrimination, violence, inequality, etc. However, around all these actions have been formed a number of representations and social imaginaries of type that are fixed in there and the young people and that are reproduced in the language, the gestures, the speeches and actions. The status of domain present in social relations and in this case from the sexual division has legitimized a series of practices that can be understood as violent actions that manifest themselves in different ways. Gender-based violence is understood as any manifestation that involves the devaluation, exclusion and even physical destruction, psychological and political of a subject because of their gender.